2018
DOI: 10.1002/qj.3399
|View full text |Cite
|
Sign up to set email alerts
|

Below‐cloud scavenging of fine and coarse aerosol particles by rain: The role of raindrop size

Abstract: Below‐cloud aerosol scavenging is an important process to remove particles from the atmosphere. In this study, both precipitation (measured with a laser disdrometer registering drops between 0.125 and 8 mm) and atmospheric aerosol particles (measured with a Passive Cavity Aerosol Spectrometer Probe registering aerosol sizes between 0.1 and 24 µm) have been sampled on a 1 min basis. Based on 6 months of outdoor measurements in León (northwest Iberian Peninsula), the scavenging coefficients were calculated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…First, aerosol composition varies with altitude (Dibb, Talbot, Scheuer, Seid, Avery, et al., 2003; Holecek et al., 2007) and, undoubtedly, precipitation samples a different air mass than ground level sampling for ambient aerosol (Dibb & Jaffrezo, 1993). Second, wet scavenging could discriminate aerosol populations based on their composition, size, density, electrical charge, and so on (Blanco‐Allegre et al., 2018; Bourcier et al., 2014; Seinfeld & Pandis, 2016). Discrimination through aerosol scavenging and formation of condensation nuclei may cause precipitation to be preferentially enriched in plant waxes, biogenic components, oxidized polar and aromatic compounds, and mineral dust, for example (Holecek et al., 2007; Simoneit & Mazurek, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…First, aerosol composition varies with altitude (Dibb, Talbot, Scheuer, Seid, Avery, et al., 2003; Holecek et al., 2007) and, undoubtedly, precipitation samples a different air mass than ground level sampling for ambient aerosol (Dibb & Jaffrezo, 1993). Second, wet scavenging could discriminate aerosol populations based on their composition, size, density, electrical charge, and so on (Blanco‐Allegre et al., 2018; Bourcier et al., 2014; Seinfeld & Pandis, 2016). Discrimination through aerosol scavenging and formation of condensation nuclei may cause precipitation to be preferentially enriched in plant waxes, biogenic components, oxidized polar and aromatic compounds, and mineral dust, for example (Holecek et al., 2007; Simoneit & Mazurek, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It was claimed the rain can clean up 40% of the PM2.5 in the study area due to the scavenging effect (Lu et al, 2019). It was observed that the fine particles with a diameter between 0.2 and 0.4 μm were mainly scavenged by rain droplets with a diameter ranging from 0.3 to 1 mm, while the coarse particles (>1 μm) could be efficiently collected by all drop sizes, mostly from raindrops larger than 1.5 mm (Blanco-Alegre et al, 2018). A geoengineering approach by the means of spraying water into the polluted air on the top of high buildings on the scale of a whole city, which aimed to mimic the rainfall, was proposed to scavenge the aerosols in the air (Yu, 2014).…”
Section: The Mechanism Of Fine Aerosol Removal By Water Sprayingmentioning
confidence: 93%
“…The volume swept by raindrops during this period was mainly due to drops with sizes N2 mm, while for the lower precipitation intensity (about 0.3 mm h −1 ) it was due to drop sizes b2 mm. Blanco-Alegre et al (2018 showed that higher volume swept by drops caused a more effective scavenging on particles between 0.12 and 0.19 μm, and there was a significant correlation between the scavenging efficiency of black carbon particles and the number of drops with diameters between 0.375 and 2.5 nm. Therefore, this precipitation event could have been responsible for removing pollutants from the atmosphere through the washout process.…”
Section: Chemical Composition Of Rainwater Samplesmentioning
confidence: 96%
“…The BCS process of different chemical species is affected by the intensity and volume of rainfall (Custódio et al, 2014;Luan et al, 2019;Pan and Wang, 2015). Furthermore, the physical parameters of precipitation (raindrop size distribution and volume swept by raindrops) are also important factors influencing the scavenging process and can also determine the chemical composition of the rainwater (Blanco-Alegre et al, 2018Fredericks and Saylor, 2019). Why is the raindrop size important?…”
Section: Introductionmentioning
confidence: 99%